Clinical signs and symptoms of Wilson disease in a real-world cohort of patients in the United States: a medical chart review study - Medici, Valentina; Kebede, Nehemiah; Stephens, Jennifer; Kunjappu, Mary; Vierling, John M. (Frontiers in Gastroenterology, 2024)
Introduction There are limited data from the United States regarding the real-world signs and symptoms of Wilson disease (WD). This retrospective, observational medical chart review was conducted to identify real-world characteristics of patients with WD in the United States, as well as WD signs and symptoms at diagnosis and over time. Methods De-identified clinical data were abstracted from medical charts of US patients diagnosed with WD between January 1, 2012, and June 30, 2017. Hepatic, neurologic, and psychiatric biochemical findings, signs, and symptoms were characterized at diagnosis and follow-up/during treatment. Results In total, 225 WD patients were included in the study. The mean (SD) age at diagnosis was 24.7 (9.8) years, and 65.3% were male. Median (Q1–Q3) follow-up after diagnosis was 39.5 (33.8–60.4) months. The most common disease presentation at WD diagnosis was combined neurologic/psychiatric and hepatic (52.9%), followed by neurologic/psychiatric (20.0%), hepatic (16.9%), and asymptomatic (10.2%). Common clinical characteristics at diagnosis were Kayser-Fleischer rings (77.2%), low ceruloplasmin levels (95.2%), high hepatic copper (97.8%), elevated 24-hour urinary copper excretion (90.2%), and abnormal liver function tests (38.7%–85.1%). At diagnosis, the most common biochemical findings or hepatic sign/symptoms were abnormal liver enzymes (50.7%), abdominal pain (16.6%), and fatigue (15.7%). The most common neurologic signs/symptoms were headache (18.3%), dysarthria (17.4%), and ataxia (17.0%). Common psychiatric signs/symptoms included anxiety/depression/other mood changes (36.2%), emotional lability (12.8%), and increased irritability/anger outbursts (9.2%). Prevalence of biochemical abnormalities or signs/symptoms among patients at diagnosis and after ~1-year follow-up were neurologic (60.1% and 44.0%), hepatic (69.6% and 37.8%), and psychiatric (53.7% and 37.6%), respectively. Common new onset symptoms at ~1-year post-WD diagnosis were abnormal liver enzymes (5.6%), headache (6.2%), and anxiety/depression/other mood changes (7.2%). Conclusions These real-world, descriptive data highlight the clinical complexity and heterogeneity of WD and the need for better education about diagnostic testing and multidisciplinary support. Although rare, the neurologic, psychiatric, and hepatic signs/symptoms of WD have a substantial clinical impact.